Smart Hybrida Power Hydroponics Based On The Internet Of Things - Mumtaza, Habil; Syaifurrahman, Syaifurrahman; Hadary, Ferry (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2026)
The hydroponic system is a method of cultivating plants without using soil, but instead utilizing nutrient solutions as a planting medium. However, monitoring and controlling important parameters such as TDS, pH, temperature, and water level manually is considered inefficient and prone to errors. To overcome this, this study designed and implemented an intelligent hydroponic system based on the Internet of Things (IoT) that is able to monitor and control the quality of nutrient solutions automatically. This system uses an ESP-32 microcontroller connected to several sensors, namely a TDS sensor (SEN0244), pH sensor (SEN0161), temperature sensor (DS18B20), and ultrasonic sensor (A02YYUW). For control, actuators are used in the form of peristaltic pumps and solenoid valves. All data from the sensors is displayed in real-time via LCD and a smartphone application connected to the Firebase database. This system is also designed with a hybrid power source, namely utilizing PLN electricity as the main source and solar power as a backup through the Automatic Transfer Switch (ATS) system. The test results show that the system works well, as evidenced by the accuracy of the TDS sensor of 99.35%, the pH sensor of 97.16%, the temperature sensor of 96.23%, and the ultrasonic sensor of 97.02%. With automatic monitoring and control capabilities, this system is considered capable of increasing efficiency and effectiveness in sustainable hydroponic cultivation.